Spiritual Awakening: A Guide to Spiritual Life in Congregations - Ackerman, John, (Rowman & Littlefield Publishers, 1994)
Ackerman, parish pastor, spiritual director, and consultant on spiritual formation, provides an excellent guide for clergy desiring a congregation-wide approach to developing spirituality rooted in the life of the congregation. A six-week program focuses on developing individuals' spirituality in small groups and includes leader training and course plans. Practical suggestions assist in developing the "corporate spirituality" of congregations.